Determine The PH Domaine of PLC-gamma in the Egg of Starfish during Fertilization - Rana Hussein Naser (Journal of Global Pharma Technology, 2016)
The PLC gamma function in fertilization has been indispensable over the years of researches. The fertilization and the insight communications with the human beings, plants and animals started from the beginning of human life. In this study, the PH-domain of PLCγ will be fused with GFP and this PH-GFP fusion protein will be used for localization studies in the starfish Patiria miniate.Keywords: Domaine; PLC-gamma; egg; Fertilization